Characteristics of oil crops and their geographical distribution in the governorates of the Middle Euphrates (Journal of the College of Basic Education, 2023)
The study aims to study the spatial variation of the cultivation of oil crops in the governorates of the Middle Euphrates, the period (2012-2021), its trends, growth and development, and to know the changes that occurred between the years (2012-2021), and the extent of the relationship between natural and human factors and their impact on that variation. For the characteristics of oil crops in the study area based on the descriptive and analytical method to show the geographical distribution of area, production and productivity.